The elements of Hittite - Hout, Theo P. J. van den. (Cambridge)
xiii, [2], 204 s.
Keywords: Hittite is the earliest attested Indo-European language and was the language of a state which flourished in Asia Minor in the second millennium BC. This exciting and accessible new introductory course, which can be used in both trimester and semester systems, offers in ten lessons a comprehensive introduction to the grammar of the Hittite language with ample exercises both in transliteration and in cuneiform. It includes a separate section of paradigms, a grammatical index, as well as a list of every cuneiform sign used in the book. A full glossary can be found at the back. The book has been designed so that the cuneiform is not essential and can be left out of any course if so desired. The introduction provides the necessary cultural and historical background, with suggestions for further reading, and explains the principles of the cuneiform writing system.